* Site-Outage Notice: Our engineering elves will be tweaking the Shmoop site from Monday,
December 22 10:00 PM PST to Tuesday, December 23 5:00 AM PST. The site will be unavailable during this time.

Substituting 3 for x produces the new expression 4(3) + 5. Simplifying this new expression gives us 12 + 5 = 17. Hey—that is how old you are! If we are correct within 5 years, you owe us a dollar.

Example 2

Evaluate the expression 2y + y^{2} if y = 4.

Substitute 4 for y to find that 2(4) + (4)^{2}. Then work out the arithmetic to find that 8 + 16 = 24.

Example 3

If y = - 4, evaluate the expression 2y + y^{2}.

Substitute - 4 for y to find that 2(- 4) + (- 4)^{2}. Simplify to find that - 8 + 16 = 8.